Application of Stochastics Dominance via Quantile Regression in Analysis of Arbitrage Opportunities Market Efficiency and Investors Preferences - Moslem Peymany Foroushany (University of Tehran, 2021)
Objective: The stochastic dominance theory has extensively employed in various financial fields because it is not necessary to assume a specific distribution of returns, such as normal distribution. In this research, one of its new applications has been used to identify arbitrage opportunities and consequently, to evaluate the efficiency of the market and also to analyse the investor preferences. Methods: To this end, a new approach of estimating stochastic dominance, the quantile regression method is utilized to perform the stochastic dominance test on the daily returns of the Tehran Stock Exchange total index close values over a period of 19 years (from September 1999 to February 2019) that contains different bullish and bearish market conditions. Results: Data analysis suggests that no evidence has been found to reject the dominance of cumulative distribution of returns between the two periods. Thus, the non-rejection of the statistical hypothesis of the first-order stochastic dominance indicates the possibility of obtaining arbitrage profit and on the other hand, the second-order stochastic dominance test rejects the market efficiency hypothesis. The existence of a third-order stochastic dominance can also be seen as a sign of the herd behavior of investors during the upward market conditions. Conclusion: The results indicate the existence of arbitrage opportunities in the Tehran Stock Exchange between bullish and bearish market conditions. Other results of this study, do not confirm the Tehran Stock Exchange efficiency hypothesis, which is consistent with most previous research about the market efficiency of the Tehran Stock Exchange. These findings also imply that risk-averse investors tend to invest in market growth cycles and suggest the existence of herd behavior during these periods.